2014
DOI: 10.1063/1.4863257
|View full text |Cite
|
Sign up to set email alerts
|

Quasi magnetic isotropy and microwave performance of FeCoB multilayer laminated by uniaxial anisotropic layers

Abstract: A Fe0.7Co0.3-B multilayer was laminated by three Fe0.7Co0.3-B ferromagnetic sublayers prepared by composition gradient sputtering. Three Fe0.7Co0.3-B ferromagnetic sublayers have their individual directions of uniaxial magnetic anisotropy, and the easy magnetic axis of neighboring sublayer successively rotates 60° in the film plane. It is exciting that a quasi magnetic isotropy was achieved in the designed multilayer with a quasi-isotropic hysteresis loop and quasi-isotorpic ferromagnetic resonance around 3.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Chai et al [19] reported an omnidirectional rotatable anisotropy in ferrite doped CoFe thin film. Very recently, we reported quasi magnetic isotropic multilayers with a high omnidirectional permeability up to 3.7 GHz piled up by UMA FeCoB films as building blocks [20].…”
Section: Introductionmentioning
confidence: 99%
“…Chai et al [19] reported an omnidirectional rotatable anisotropy in ferrite doped CoFe thin film. Very recently, we reported quasi magnetic isotropic multilayers with a high omnidirectional permeability up to 3.7 GHz piled up by UMA FeCoB films as building blocks [20].…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The E-field was applied across substrate and the magnetic field was applied along the in-plane (IP) direction, vertical to the microwave propagation. As an E-field is applied, the piezoelectric substrate undergoes a tensile or compressive deformation and that strain can be coherently transferred to magnetic films resulting in an effective magnetic field H eff through the magnetoelastic effect.…”
Section: Voltage Control Of Fmr Through Strain/stressinduced Me Couplmentioning
confidence: 99%
“…Lots of layered strain/stress dominated multiferroic heterostructures such as bulk/bulk, [27][28][29][30][31] thin film/bulk [32][33][34][35][36][37][38][39][40][41][42][43][44][45] and thin film/thin film 47 magnetic/ferroelectric or magnetic/piezoelectric heterostructures were demonstrated in this paper. By applying voltage across the ferroelectric/piezoelectric layer, the ferroelectric/piezoelectric layer generates a large strain/stress energy change that influence the magnetic layer, therefore, change the effective magnetic anisotropy energy which lead to an effective FMR field or frequency change.…”
Section: Introductionmentioning
confidence: 99%
“…To find the desired materials with IHP in the GHz range is still a challenge. For instance, a variety of theoretical 5 6 7 and experimental works focus on both high 8 9 10 and isotropic 11 12 13 14 15 16 17 18 permeability in the GHz range of granular films 9 and multilayers 10 of magnetic alloys, ferrites and their composites.…”
mentioning
confidence: 99%
“…Searching for the isotropic permeability in the GHz range is another important topic in magnetic thin films. For instance, magnetic thin films with rotatable stripe domain 42 43 44 45 46 , composite-anisotropy multilayer as well as crossed anisotropies multilayer 11 12 13 14 15 16 17 18 are intensively investigated. The rotatable stripe domain was discovered firstly in Permalloy films in 1961 42 , and then in many other magnetic thin films 43 44 45 46 .…”
mentioning
confidence: 99%